Metaphor and Simile as Expressions of Emotion Portrayed in the Novel The Devil Wears Prada - Kevin Jie (Prologue: Journal on Language and Literature, 2021)
The research aims to analyze metaphor and simile as the expression of emotion portrayed in the novel The Devil Wears Prada by Lauren Weisberger. The objectives of this research are to identify the tenor of metaphor and the simile within the novel and to analyze metaphor and the simile to express the expression of emotion within the novel. The theory used in this research is the semantic theory by Geoffrey Leech about the figurative language The method used in this research is the qualitative descriptive way. The data contained in this research is divided into primary and secondary data. Primary data is the novel The Devil Wears Prada, and the secondary data are sourced from the articles, journals, e-books, books, and other references related to this research. The researcher found several types of figurative language such as metaphor and simile within the novel. Each of the figurative languages expresses the expression of emotion such as happy emotion, angry emotion, fear emotion, and love emotion. The research shows that metaphor is the most frequent type of figurative language found and the most frequent type of figurative language that expresses the emotion within the novel.